Standardization and simplification of vaccination records. (April 2014) - Maurer, Wolfgang; Seeber, Lea; Rundblad, Gabriella; Kochhar, Sonali; Trusko, Brett; Kisler, Bron; Kush, Rebecca; Rath, Barbara
<x xml:space="preserve">Abstract</x> The majority of vaccines are administered during childhood. Vaccination records are important documents to be kept for a lifetime, but the documentation of immunization events is poorly standardized. At the point of care, paper records are often unavailable, making it impossible to obtain accurate vaccination histories. Vaccination records should include batch specifications to allow the tracking of licensed vaccines in cases of recall. The WHO have generated the International Certificate of Vaccination or Prophylaxis for the documentation of childhood and travel vaccinations as well as seasonal and booster immunizations. When moving vaccination records into the digital age, data standards and interoperability need to be considered. The ideal vaccination record should facilitate the interpretation of safety reports and promote a data continuum from pre-licensure trials to post-marketing surveillance. The current article describes which data elements are essential, and how vaccination documentation could be streamlined and simplified.